Adhesion and virulence properties of native Metarhizium fungal strains from Burkina Faso for the control of malaria vectors - Issiaka Sare; Francesco Baldini; Mafalda Viana; Athanase Badolo; Florencia Djigma; Abdoulaye Diabate; Etienne Bilgo (Parasites & Vectors, 2023)
Abstract Background Local strains of the entomopathogenic fungus Metarhizium pingshaense in Burkina Faso have demonstrated remarkable virulence against malaria vectors, positioning them as promising candidates for inclusion in the future arsenal of malaria control strategies. However, the underlying mechanisms responsible for this virulence remain unknown. To comprehend the fungal infection process, it is crucial to investigate the attachment mechanisms of fungal spores to the mosquito cuticle and explore the relationship between virulence and attachment kinetics. This study aims to assess the adhesion and virulence properties of native Metarhizium fungal strains from Burkina Faso for controlling malaria vectors. Methods Fungal strains were isolated from 201 insects and 1399 rhizosphere samples, and four strains of Metarhizium fungi were selected. Fungal suspensions were used to infect 3-day-old female Anopheles coluzzii mosquitoes at three different concentrations (106, 107, 108 conidia/ml). The survival of the mosquitoes was measured over 14 days, and fungal growth was quantified after 1 and 24 h to assess adhesion of the fungal strains onto the mosquito cuticle. Results All four fungi strains increased mosquito mortality compared to control (Chi-square test, χ2 = 286.55, df = 4, P < 0.001). Adhesion of the fungal strains was observed on the mosquito cuticle after 24 h at high concentrations (1 × 108 conidia/ml), with one strain, having the highest virulent, showing adhesion after just 1 h. Conclusion The native strains of Metarhizium spp. fungi found in Burkina Faso have the potential to be effective biocontrol agents against malaria vectors, with some strains showing high levels of both virulence and adhesion to the mosquito cuticle. Graphical Abstract